Inhibitory effect of fungoid chitosan in the generation of aldehydes relevant to photooxidative decay in a sulphite-free white wine. (15th July 2021) - Castro Marin, Antonio; Stocker, Pierre; Chinnici, Fabio; Cassien, Mathieu; Thétiot-Laurent, Sophie; Vidal, Nicolas; Riponi, Claudio; Robillard, Bertrand; Culcasi, Marcel; Pietri, Sylvia
Highlights: Fungoid chitosan reduces the generation of aldehydes during wine photo-oxidation. In extended oxidative conditions SO2 is a poorer wine anti-browning agent than chitosan. Sulphites better control free acetaldehyde but not glyoxylic acid amounts. In wines chitosan can mitigate the browning while preserving catechin amounts. Abstract: The reaction pathways were investigated by which a fungoid chitosan (CsG) may protect against photooxidative decay of model solutions and a sulphite-free white wine. Samples containing CsG were dark incubated for 2 days before exposure to fluorescent lighting for up to 21 days in the presence of wine like (+)-catechin and/or iron doses. In both systems CsG at winemaking doses significantly reduced the photoproduction of acetaldehyde and, to a better extent, glyoxylic acid, two key reactive aldehydes implicated in wine oxidative spoilage. After 21 days, CsG was two-fold more effective than sulphur dioxide in preventing glyoxylic acid formation and minimizing the browning of white wine. Among the antioxidant mechanisms involved in CsG protective effect, iron chelation, and hydrogen peroxide quenching were demonstrated. Besides, the previously unreported tartrate displacement from the [iron(III)-tartrate] complex was revealed as an additional inhibitory mechanism of CsG under photo-Fenton oxidation conditions.